Estudo mineralógico em rochas do Stock Itaju do Colônia, sul da Bahia - Pimenta, Adjanine Carvalho Santos (2016)
The alkaline magmatism in the State of Bahia is characterized by the occurrence of several bodies that occur in different regions and ages. One of the most significant expressions of this magmatism is represented by the Alkaline Province South of Bahia. Among the intrusion of this province, there is the Itaju do Colônia Stock with about 1km² area, which consists predominantly of nepheline syenite and sodalite syenite. Currently, this stock is the only one in Brazil where there are economic deposits of sodalite syenite intense blue color, commercially known as ‘Bahia Blue Granite’. This study brings together data from various analytical techniques mineralogical characterization as scanning electron microscopy, mineral chemistry analyses and rock geochemistry. Several minerals were first described by this study in Itaju do Colônia, such as pyrochlore, ancylite, bastnäsite, thorite, keiviite, xenotime and euxenite. The information obtained allowed us to infer the existence of an important metasomatic event materialized by the presence of sphalerite, barite, galena, fluorite and fluorcarbonates. Rock geochemistry analyses confirmed the miaskitic peralkaline character of this stock, and found a significant enrichment of some trace elements such as Zr (up to 1,520 ppm), Nb (up to 470 ppm), Th (up to 79 ppm), Zn (75 ppm), Ce (44 ppm) and La (22 ppm). The ETR spectra are weakly fractionated and marked by negative Eu anomalies.